Atlas of Fshr expression from novel reporter mice - Hongqian Chen; Hui-Qing Fang; Jin-Tao Liu; Shi-Yu Chang; Li-Ben Cheng; Ming-Xin Sun; Jian-Rui Feng; Ze-Min Liu; Yong-Hong Zhang; Clifford J Rosen; Peng Liu (eLife)
The FSH-FSHR pathway has been considered an essential regulator in reproductive development and fertility. But there has been emerging evidence of FSHR expression in extragonadal organs. This poses new questions and long-term debates regarding the physiological role of the FSH-FSHR, and underscores the need for reliable, in vivo analysis of FSHR expression in animal models. However, conventional methods have proven insufficient for examining FSHR expression due to several limitations. To address this challenge, we developed Fshr-ZsGreen reporter mice under the control of Fshr endogenous promoter using CRISPR-Cas9. With this novel genetic tool, we provide a reliable readout of Fshr expression at single-cell resolution level in vivo and in real time. Reporter animals were also subjected to additional analyses,to define the accurate expression profile of FSHR in gonadal and extragonadal organs/tissues. Our compelling results not only demonstrated Fshr expression in intragonadal tissues but also, strikingly, unveiled notably increased expression in Leydig cells, osteoblast lineage cells, endothelial cells in vascular structures, and epithelial cells in bronchi of the lung and renal tubes. The genetic decoding of the widespread pattern of Fshr expression highlights its physiological relevance beyond reproduction and fertility, and opens new avenues for therapeutic options for age-related disorders of the bones, lungs, kidneys, and hearts, among other tissues. Exploiting the power of the Fshr knockin reporter animals, this report provides the first comprehensive genetic record of the spatial distribution of FSHR expression, correcting a long-term misconception about Fshr expression and offering prospects for extensive exploration of FSH-FSHR biology.